Other people's money: does external debt improve economic growth performance of Frontier market economies? - Musonda, Mary-Anne (Graduate School of Business (GSB), 2020)
Sources of long-term growth in an economy hinge on the productive potential of the country. Major contributing factors in the production of an economy include the population representing the labour force, advanced technological inputs, investment and capital accumulation. External debt can be viewed as a critical additional income stream to enhance the productive capacity of an economy, and to supplement internal investment in cases where internal investment is not sufficient to fund economic growth focused projects and activities. However, external debt also has devastating effects on economic growth if left unmonitored or misused. Frontier Market Economies (FMEs), which are economies developing into Emerging Market Economies (EMEs), are amongst the fastest growing in the world with this growth projected to continue into the future. Yet, these countries are often forced to rely on external financing because of insufficient local markets. It is thus of critical importance to ascertain whether external debt has been a benefit or hindrance to these economies in the past, so as to develop appropriate debt management strategies to support their growth in the future. The effect of external debt on economic growth in eight FMEs is examined in this study using the system Generalized Methods of Moments (GMM) model to test for a linear relationship as well as an inverted U-shape curve between external debt and economic growth. An inverted U-shape curve implies that a threshold point exists which signals a point beyond which an economy becomes over-indebted, thus hampering economic growth. The findings of this study reveal that external debt has a positive and significant impact on economic growth in the FMEs studied. However, there was no inverted U-shape curve between the two variables. Instead a U-shape exists and thus, no maximum level of borrowing was found for the FMEs. Appropriate debt management strategies are discussed in light of the findings. Therefore, with improved demographics and strong consumption growth mixed with a lack of connection from world economics, FMEs have the potential to be part of the rapid growing economies in the world.